Creatividad y su incidencia en el proceso de enseñanza aprendizaje de los estudiantes de básica media de la Unidad Educativa Federico Froebel del cantón Babahoyo - Gomez Cueva, Sonia Karina (2019)
Creative education responds to the new scenarios that affect the formative processes in the teaching-learning model, focused on the incidence of the student. The preparation for autonomous work, the learning of cognitive skills, the adaptation to emergent situations, the development of the entrepreneurial spirit and the creative capacity, the diversification in the ways of learning and teaching, arise as demands of an innovative formation. The experiences developed of the implementation of creative education in middle school students, require previously to have policies and strategies that allow to enhance a culture oriented towards change, creating or strengthening organizations that mobilize internal initiatives, which articulate projects in the medium and long term, which support training, innovative actions via projects and research in pedagogy. The experiences that arise from this research will support the development of creativity in teacher-student relationships and in the performance of subjects. The research carried out in the Federico Froebel educational unit, is emanated from the basic education career, in the Faculty of Social and Educational Legal Sciences of the Technical University of Babahoyo, in which the educational intervention was intended to teach thinking about creatively, through disciplinary content, they showed important results in improving the creativity of middle school students, exposed to experiences. They were applied in all the subjects taught. The application of inventories or questionnaires that diagnose creative talent before and after innovative work, shows significant changes in the improvement of traits such as imagination, confidence, independence and inventiveness, in addition to the improvement in the performance of the subjects. The dissemination and use of creative techniques can be a valuable contribution to improve aspects that affect the quality of student learning